THE RELATIONSHIP BETWEEN NURSE'S KNOWLEDGE REGARDING HEALTH LAWS AND THE PERFORMANCE OF NURSES AT INTAN HUSADA HOSPITAL GARUT - Iman Nurjaman; Ina Saparlina (CV SWA Anugerah, 2023)
The Health Law is one of the legal foundations governing the competence of the nursing profession. Nurses need to increase their understanding and awareness of the law to be able to make the right decisions in real-life situations. Increased legal understanding must also be accompanied by changes in nurse behavior to increase efficiency to support the quality of service to clients. This study aims to analyze the relationship between nurses' knowledge about the Health Law to the performance of nurses at Intan Husada Garut Hospital. The study was conducted using a cross-sectional research method with random proportional sampling. The research instrument used was a questionnaire of nurses' knowledge regarding the Nurse Health and Performance Law. The number of participants in this study was 100 people. Most respondents are knowledgeable about health law (80.0%) and highly productive (70.0%). The results of bivariate statistics obtained that the relationship between knowledge of Health Law and Nurse Performance r (Rho) = 0.491 with a significance value (p-value) of 0.000<0.05 which states that there is a moderate and positive patterned relationship, meaning that the more nurse knowledge about Health Law, the higher the Nurse Performance. The questionnaire successfully identified a link between knowledge of Health Law and nurse performance, which is valuable to policymakers and researchers. Time constraints because respondents fill out questionnaires while working. More research and in-depth interviews are needed to explore other factors that affect nurse performance.